Investigating the prevalence and correlates of depression and stress in older adults: A nation-wide survey in Libya - Mohamed Ali; Alhadi M. Jahan (Archives of Gerontology and Geriatrics Plus)
This cross-sectional study aims to examine the depressive symptoms and stress among older adults. A convenience sample (n = 547) of older adults aged 60+ years was recruited from various regions in Libya. The WHO-5 and PSS-10 were used to assess depression and stress levels. The level of depressive symptoms and stress were 68 % and 71.5 %, respectively, with males reported more depression and stress than females (p ˂ 0.05). A combination of stress and family status significantly associated with levels of depression among the participants. This study provides important insights into the psychological health status of older adults in Libya. The high levels of depression and stress, as well as the identified correlates, shed light on the factors influencing mental well-being in this vulnerable population. These findings can serve as a foundation for the development of targeted interventions aimed at promoting the mental health of older adults in Libya.